Structural Stability of Pyrochlore Manganate In2Mn2O7 Under High Pressure - Li, Hui; Ma, Shuailing; Ye, Jili; Wang, Xin (Frontiers in Physics, 2021)
The pyrochlore manganate In2Mn2O7 is a very promising ferromagnetic semiconductor material, which has a good application prospect in spin transport due to its very low electron effective mass, high Curie temperature and structural stability. In this paper, In2Mn2O7 with pyrochlore structure was successfully prepared by high temperature and high pressure combined with sol-gel method, and the in-situ high-pressure X-ray diffraction experiment was carried out on it. The results showed that the structure of In2Mn2O7 was very stable in the pressure range of 0-29.0 GPa, and its bulk modulus was given. This lays a foundation for the application of In2Mn2O7 in extreme environments.